Association of Heterophil/Lymphocyte Ratio with Intestinal Barrier Function and Immune Response to Salmonella enteritidis Infection in Chicken - Mamadou Thiam; Astrid Lissette Barreto Sánchez; Jin Zhang; Maiqing Zheng; Jie Wen; Guiping Zhao; Qiao Wang (Animals, 2021)
The heterophil/lymphocyte (H/L) ratio has been extensively studied to select poultry that are resistant to environmental stressors. Chickens with a low H/L ratio are superior to the chickens with a high H/L ratio in survival, immune response, and resistance to Salmonella infection. However, this disease resistance ability is likely to be associated with enhanced intestinal immunity. Therefore, to expand our understanding of these underlying resistance mechanisms, it is crucial to investigate the correlation between the H/L ratio as a blood immune indicator in live chickens and the intestinal barrier function and immunity. Jinxing yellow chickens H/L line one-day-old were divided into non-infected (NI) and Salmonella enteritidis infected (SI) at 7-days old. After dividing the birds into NI and SI, blood samples were taken for H/L ratios determination, and subsequently, birds from the SI group were infected with Salmonella enteritidis (SE). We assessed the effects of SE infection on the (i) goblet cells number from the ileum and caecum gut-segments, (ii) ileal mucosa morphology, and (iii) immune gene mRNA expressions from the ileum and caecum of NI and SI chickens at 7 and 21 days-post-infection (dpi). We found that the H/L ratio was negatively correlated with most intestinal immune indices, particularly with the goblet cells number and with IL-1β, IL-8, and IFN-γ ileal expressions. In conclusion, these results suggest that the H/L ratio is associated with the intestinal barrier and immune response for SE clearance and that the chickens with a low H/L ratio displayed enhanced intestinal immunity. This study expands the current knowledge that is related to using the H/L ratio to select and breed resistant broiler chickens.